MELISSOPALYNOLOGICAL ANALYSIS OF HONEY FROM DOLAGO VILLAGE, CENTRAL SULAWESI - Rasyiid, Mustafid; Iqbal, Moh.; Paserang, Asri Pirade; Budiono, Yudhistira Kristinov; Nugraha, Muh. Ardian Satrio; Wiguna, Triadhy (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
One thing that honeybees create that is very beneficial to human health is honey. Consequently, honey is frequently faked. With melissopalynology analysis, honey quality can be ascertained. A technique for analyzing pollen in honey to ascertain its botanical and geographic origin is called melissopalynology analysis.This study uses melissopalynology to analyze the quality and pollen composition of honey produced by Apis cerana bees in Dolago Village, Central Sulawesi. The research consists of five stages: collecting honey, extracting pollen from it using a modified acetolysis method, identifying pollen, classifying honey, and last, absolute pollen count. The analysis identified 11 plant species contributing to honey production, with Cocos nucifera as the predominant pollen (70%). Classified as unifloral honey with Group IV pollen richness, this research confirms the high quality and unique floral origin of Dolago honey, emphasizing its potential for local economic development.